Predicting health behaviors across Belgium and France during the first wave of COVID-19 pandemic. (December 2022) - Schmitz, Mathias; Wollast, Robin; Bigot, Alix; Luminet, Olivier
The objective of the current research was to investigate how a series of psychological factors may underlie two COVID-19 health behaviors, and how a contextual factor (country of residence) could shape their influence. Cross-sectional results from the first pandemic wave ( N Belgium = 4878, N France = 1071) showed that handwashing and social contacts limitation are predicted by a unique set of psychological variables that holds across Belgium and France, despite their distinct lockdown-policies strictness. In practice, policy-makers could leverage on these unique predictors and fine-tune their strategies accordingly to promote adherence to each measure while generalizing it across similar nations.